2004
DOI: 10.3171/foc.2004.16.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suprascapular nerve neurotization after nerve grafting or transfer in the treatment of brachial plexus traction lesions

Abstract: Object The aim of this retrospective study was to evaluate the restoration of shoulder function by means of supra-scapular nerve neurotization in adult patients with proximal C-5 and C-6 lesions due to a severe brachial plexus traction injury (BPTI). The primary goal of brachial plexus reconstructive surgery was to restore the biceps muscle function and, secondarily, to reanimate shoulder function. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Other surgeons (8) have proposed that poor results might be related to double lesions of the suprascapular nerve. Double lesions, however, were not identified in our previous studies if the suprascapular nerve was explored in the scapular notch.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other surgeons (8) have proposed that poor results might be related to double lesions of the suprascapular nerve. Double lesions, however, were not identified in our previous studies if the suprascapular nerve was explored in the scapular notch.…”
Section: Discussionmentioning
confidence: 98%
“…Transfer of the accessory nerve to the suprascapular nerve is widely used to reconstruct shoulder abduction and external rotation (7). Indeed, the results of this transfer are superior to grafts from the non-avulsed C5 root to the suprascapular nerve (3,8,9). The accessory nerve has also been used to reconstruct the musculocutaneous nerve or lateral cord, with encouraging results (1,4,11,12,13).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Since then, it has been extensively used by many workers. [7][8][9] In a meta-analysis, Merrell et al 10 concluded that transferring the SAN into the SSN represented the most suitable option for restoration of shoulder abduction. Nagano 11 noted that double-or triple-level injury in the SSN is a frequent occurrence that could possibly explain the poor postoperative nerve transfer results associated with weakness in the infraspinatus muscle.…”
Section: Discussionmentioning
confidence: 99%